The Democratic Imperative to Address Sexual Equality Rights in Schools. Issue 5 (18th October 2013) - Gereluk, Dianne
Abstract Issues of sexual orientation elicit ethical debates in schools and society. In jurisdictions where a legal right has not yet been established, one argument commonly rests on whether schools ought to address issues of same‐sex relationships and marriage on the basis of civil equality, or whether such controversial issues ought to remain in the private sphere. Drawing upon an antiperfectionist liberal framework, Dianne Gereluk argues that schools have an obligation to educate students in two important ways. First, students must develop an awareness and understanding of the range of acceptable and permissible ways of life that may lead to human flourishing. Second, students must understand the requisite protections and recognition afforded to individuals in a pluralist society.